Serglycin: At the Crossroad of Inflammation and Malignancy - Korpetinou, Angeliki; Skandalis, Spyros S.; Labropoulou, Vassiliki T.; Smirlaki, Gianna; Noulas, Argyrios; Karamanos, Nikos K.; THEOCHARIS, ACHILLEAS D. (Frontiers in Oncology, 2014)
Serglycin has been initially characterized as an intracellular proteoglycan expressed by hematopoietic cells. All inflammatory cells highly synthesize serglycin and store it in granules, where it interacts with numerous inflammatory mediators, such as proteases, chemokines, cytokines and growth factors. Serglycin is implicated in their storage into the granules and their protection since they are secreted as complexes and delivered to their targets after secretion. During the last decade, numerous studies have demonstrated that serglycin is also synthesized by various non-hematopoietic cell types. It has been shown that serglycin is highly expressed by tumor cells and promotes their aggressive phenotype and confers resistance against drugs and complement system attack. Apart from its direct beneficial role to tumor cells, serglycin may promote the inflammatory process in the tumor cell microenvironment thus enhancing tumor development. In the present review, we discuss the role of serglycin in inflammation and tumor progression.